Retinal phagocytes in age-related macular degeneration - Kim, Soo-Young (Macrophage (Houst), 2015)
Age-related macular degeneration (AMD) is the leading cause of blindness in industrial countries. Vision loss caused by AMD results from geographic atrophy (dry AMD) and/or choroidal neovascularization (wet AMD). Presently, the etiology and pathogenesis of AMD is not fully understood and there is no effective treatment. Oxidative stress in retinal pigment epithelial (RPE) cells is considered to be one of the major factors contributing to the pathogenesis of AMD. Also retinal glia, as scavengers, are deeply related with diseases and could play a role. Therefore, therapeutic approaches for microglia and Müller glia, as well as RPE, may lead to new strategies for AMD treatment. This review summarizes the pathological findings observed in RPE cells, microglia and Müller glia of AMD murine models.